Hubungan Keterlibatan Ayah dalam Pengasuhan dengan Kecerdasan Emosional Remaja - Sari, Ayu Ratna; Roslita, Riau; Anggreny, Yecy (Jurnal Cakrawala Promkes, 2021)
Indonesia has a demographic bonus where the number of young people is quite large than the old generation and children. Youth in Pekanbaru City reached 20,095% or 234.916 people. The problem is from the preliminary studies results that many adolescents have low emotional intelligence because they are considered less skilled in socializing and are motivated because of social media and electronic media. This study aims to determine the relationship between father involvement in parenting with adolescent emotional intelligence. This research is a quantitative study with a cross-sectional design. The sample in this study were 116 adolescents of Air Cold Village, Bukit Raya Pekanbaru District. Sampling using the Non-Probability technique with the snowball sampling method. Researchers used a questionnaire to collect data. This study uses a bivariate analysis, namely Chi-Square. The results showed that fathers' involvement in parenting was in the high category, namely 92.2% of 107 people. Kidney intelligence is in the percentage of 82.8% of 96 people. Thus, there is a positive or significant relationship between fathers' involvement in parenting and adolescent emotional intelligence with a value of P = 0.008 (p <0.05). With these results, it is hoped that nurses can motivate nurses to promote health-related to adolescent psychology through the Youth Family Development Program and the Youth Care Health Program. This is important as an effort to foster adolescent emotional intelligence.  Keywords: Emotional Intelligence, Father’s involvement, Parenting, Adolescents